2018
DOI: 10.3390/molecules23071636
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fatty Acids in Milk Fat and the Influence of Selected Factors on Their Variability—A Review

Abstract: Fatty acids (FAs) of milk fat are considered to be important nutritional components of the diets of a significant portion of the human population and substantially affect human health. With regard to dairy farming, the FA profile is also seen as an important factor in the technological quality of raw milk. In this sense, making targeted modifications to the FA profile has the potential to significantly contribute to the production of dairy products with higher added value. Thus, FAs also have economic importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
123
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(159 citation statements)
references
References 210 publications
(277 reference statements)
6
123
1
2
Order By: Relevance
“…In all analysed samples of milk and yogurts, oleic acid (C18:1 cis9) was the most dominant acid of the MUFA group (Table 1). This acid is important from a nutritional point of view since it has anti-cancer and anti-atherogenic properties (Hanuš et al, 2018). A significantly higher content (P<0.05) of this acid was found in goat milk and yoghurts than in sheep and cow milk and yoghurts ( Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…In all analysed samples of milk and yogurts, oleic acid (C18:1 cis9) was the most dominant acid of the MUFA group (Table 1). This acid is important from a nutritional point of view since it has anti-cancer and anti-atherogenic properties (Hanuš et al, 2018). A significantly higher content (P<0.05) of this acid was found in goat milk and yoghurts than in sheep and cow milk and yoghurts ( Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…A large percentage of fat in dairy products is saturated compounds but they are also a source of fat‐soluble vitamins and unsaturated fats, including omega‐3s (Canada’s Food Guide, ). So, milk fat contains fatty acids which are considered essential nutrients in the diet that can affect human health (Hanuš, Samková, Křížová, Hasoňová, & Kala, ). Lipids provide twice as much energy as the same quantity of carbohydrates and proteins (Ehirim & Onyeneke, ).…”
Section: Resultsmentioning
confidence: 99%
“…According to literature data the cis9,trans11 CLA isomer constitutes from 75% to over 90 % of the sum of CLA in the fat of milk and dairy products (C hin et al, 1992;Jiang et al, 1998;Lin et al, 1998;Bauman and Lock, 2006; Koba and Yanagita, 2014). Biomedical studies with animal models have demonstrated a variety of health benefits of CLA, including anticarcinogenic, antiatherogenic and antiobesity influence; the enhancement of the immune system and the antidiabetic effect (Akalln and Tokusoglu, 2003; Kee et al, 2010;Molkentin, 1999;Parodi, 2003;Park, 2009;Aydin, 2005;Yang et al, 2015;Hanuš et al, 2018). Typical concentrations of CLA in milk fat are 3-6 mg g -1 fat (Kelly et al, 1998).…”
Section: Introductionmentioning
confidence: 99%